Numerical modeling of the combustion of pre-mixed fuel in micromodule burner - Umyshev, D.R.; Dostiyarov, A.M.; Sadykova, S.B.; Iliev, I.; Dostiyarova, A.M. (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The article presents the results of numerical simulation for the combustion of pre-mixed fuel in micromodule. The study prerequisites, burner model and the initial modeling conditions are presented. It is shown that the burner has high environmental performance outside the stoichiometry zone. The dependences of temperatures on the coefficient of excess fuel are presented, which confirm the dependence of the concentration of nitrogen oxides on the excess fuel. The concluding section presents a formula for calculating the concentration of nitrogen oxides based on the temperature in the combustion zone.